Optimizing the Use of Websites and Social Media in Efforts to Improve Orthotic Prosthetic Services - Rachmat, Nur; Kristianto, Jusuf (Mandalika Journal of Medical and Health Studies, 2024)
Prosthetic Orthotic services during the COVID 19 pandemic need to be improved by optimizing the use of websites and social media. To find out what the Prosthetic Orthotic Kuspito Clinic is doing in optimizing the use of websites and social media to improve prosthetic orthotic services during the COVID-19 pandemic. Qualitative research by describing the results of direct observations and interviews with informants. Milles and Huberman's data analysis model. Research conducted at PT. Kuspito Orthotic Prosthetics in January and February 2023. Optimization of website use in an effort to improve prosthetic orthotic services is carried out by creating a website with several additional features in the form of displaying product price information, product purchasing and payment processes that can be made directly on the comfiware.com website, discounts and discounts for customers that can be accessed On the website, product payments can be paid by GoPay, bank transfers, credit cards and consulting services regarding products, through WhatsApp social media, where the access button is on the comfiware.com website display. Optimizing the use of websites and social media to improve Orthotic Prosthetic services during a pandemic has been carried out well at PT. Prosthetic Orthotic Kuspito